Peranan Green Accounting Pemoderasi Hubungan antara Green Intellecetual Capital dengan Earning Management : Studi Empiris Perusahaan IDX periode tahun 2020-2025 - Fitri Dwi Febrianti; Sugiyanto Sugiyanto; Rachmat Kartolo (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
his study is grounded in the growing shift from “profit at all cost” to “profit with purpose,” where companies are expected to balance financial performance with environmental responsibility. In the context of the green economy, Green Intellectual Capital (GIC) plays a strategic role in promoting efficient resource use, ecological awareness, and responsible business practices through integrated reporting. This research examines the effect of Green Intellectual Capital on earnings management, with Green Accounting incorporated as a moderating variable. The objective is to analyze whether Green Accounting strengthens or weakens the relationship between GIC and earnings management among companies listed on the Indonesia Stock Exchange (IDX). This study employs a quantitative associative approach using secondary data. The population consists of 150 industrial companies listed on the IDX during the 2020–2025 period, with a purposive sample of 25 firms. Panel data regression analysis and Moderated Regression Analysis (MRA) were conducted using EViews. The findings indicate that Green Intellectual Capital significantly influences earnings management. Structural capital and relational capital show a positive effect, while human capital is not significant. Green Accounting strengthens the overall relationship, although the interaction with structural capital weakens the effect. These findings provide implications for investors, creditors, and policymakers in supporting sustainable capital expenditure decisions.